Modeling the population density and losses caused by the red and Khapra flour beetle and the impurity of the flour and its effect on its qualities - Ayad Ismael (College of Education for Pure Sciences, 2009)
The regression of population density and nutrient medium weight of red flour beetle Tribolium castaneum(Herbst) were 0.993, 0.987, respectively. Whereas, in Khapra beetle Trogoderma granarum(Everts) were 0.975, 0.948, respectively. The nutrient medium weight decreased significantly in red flour beetle in comparison with Khapra beetle and the result were 186.11, 188.67 gm respectively. In Khapra beetle the fermentation size changed significantly in comparison with red flour beetle and the result was 10.43, 18.58 cm3, respectively. There was no change in absorbed water and glutine weights in both insects, but there was significant change in comparison with control in initial time, two and four months after treatment.